Neuroprotective Effect of Bexarotene in the SOD1G93A Mouse Model of Amyotrophic Lateral Sclerosis - Riancho, Javier; Ruiz-Soto, María; Berciano, María T.; Berciano, José; Lafarga, Miguel (Frontiers in Cellular Neuroscience, 2015)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by progressive weakness and muscle atrophy related to the loss of upper and lower motor neurons (MNs) without a curative treatment. There is experimental evidence suggesting that retinoids may be involved in ALS pathogenesis. Bexarotene (Bxt) is a retinoid-X receptor agonist used in the treatment of cutaneous lymphoma with a favourable safety profile whose effects have been recently investigated in other neurodegenerative diseases. In this study, we analyze the potential therapeutic effect of Bxt in the SOD1G93A mouse model of ALS. Mice were treated with Bxt or vehicle five times per week from day 60 onwards. Survival, weight and neuromuscular function studies together with histological and biochemical analyses were performed. Bxt significantly delayed motor function deterioration, ameliorated the loss of body weight and extended mice survival up to 30% of the symptomatic period. Histological analyses of the lumbosacral spinal cord revealed that Bxt markedly delayed the early motor-neuron degeneration occurring at presymptomatic stages in ALS-transgenic mice. Bxt treatment contributed to preserve the MN homeostasis in the SOD1G93A mice. Particularly, it reduced the neuronal loss and the chromatolytic response, induced nucleolar hypertrophy, decreased the formation of ubiquitylated inclusions and modulated the lysosomal response. As an agonist of the retinoic-X receptor pathway (RXR), Bxt notably increased the nuclear expression of the RXRα throughout transcriptionally active euchromatin domains. Bxt also contributed to protect the MN environment by reducing reactive astrogliosis and preserving perisomatic synapsis. Overall, these neuroprotective effects suggest that treatment with Bxt could be useful in ALS, particularly in those cases related to SOD1 mutations.